An Anthropological Linguistic Study of The Novel Man’en Gannen No. Futtoboru by Kenzaburo Oe: A Moral Crisis and Its Implications for Multicultural Learning - Iroth, Santje; Ali, Muhammad Ilham (Universitas Negeri Semarang, 2025)
This study examines the moral crisis depicted in Kenzaburo Oe's Man'en Gannen no Futtoboru and its implications for multicultural learning using an anthropological linguistic approach. Through the moral conflicts experienced by his characters, Oe shows the tension between tradition, modernity, and social change in post-war Japanese society. This study aims to explore how the moral and social discourses in the novel reflect intercultural dynamics, as well as how anthropological linguistic analysis can be used in an educational context to enhance students' understanding of multicultural awareness. This research uses a qualitative approach with critical discourse analysis to explore the narratives depicting moral crises and cultural representations in the novel. The results show that anthropological linguistics-based learning can help students understand the role of language in uncovering and mediating moral conflicts in multicultural societies.